Development of Contextual Visual Media in Increasing MTs Students' Learning Motivation - Hastuti, Euis Sri (Edubiologica, 2024)
Motivation has a strategic role in a person's learning activities, without motivation no one will learn and the learning process will not continue. The use of media in learning is very important because it makes the material presented easier to understand and makes students more motivated. Developing digital-based learning media is a good learning media to use in learning in the era of the industrial revolution 4.0 and is believed to be able to increase student motivation. The aim of this research is to develop contextual visual media that can increase student motivation. The method used in this research uses the ADDIE model developed by Dick and Carry. The research results are in the form of contextual visual media which was developed using five stages, namely analysis, design, development, implementation and evaluation. The validity test results are in the very good category, so the visual media developed is suitable for use in research. Based on the t test results of 0.012, these results indicate that the hypothesis is accepted, so it can be concluded that there is an increase in motivation after learning activities using the developed contextual visual media.